Novel p53 target gene FUCA1 encodes a fucosidase and regulates growth and survival of cancer cells. Issue 6 (16th May 2016) - Ezawa, Issei; Sawai, Yuichiro; Kawase, Tatsuya; Okabe, Atsushi; Tsutsumi, Shuichi; Ichikawa, Hitoshi; Kobayashi, Yuka; Tashiro, Fumio; Namiki, Hideo; Kondo, Tadashi; Semba, Kentaro; Aburatani, Hiroyuki; et al.
Abstract : The tumor suppressor p53 functions by inducing the transcription of a collection of target genes. We previously attempted to identify p53 target genes by microarray expression and ChIP‐sequencing analyses. In this study, we describe a novel p53 target gene, FUCA1, which encodes a fucosidase. Although fucosidase, α‐l ‐1 (FUCA1) has been reported to be a lysosomal protein, we detected it outside of lysosomes and observed that its activity is highest at physiological pH. As there is a reported association between fucosylation and tumorigenesis, we investigated the potential role of FUCA1 in cancer. We found that overexpression of FUCA1, but not a mutant defective in enzyme activity, suppressed the growth of cancer cells and induced cell death. Furthermore, we showed that FUCA1 reduced fucosylation and activation of epidermal growth factor receptor, and concomitantly suppressed epidermal growth factor signaling pathways. FUCA1 loss‐of‐function mutations are found in several cancers, its expression is reduced in cancers of the large intestine, and low FUCA1 expression is associated with poorer prognosis in several cancers. These results show that protein defucosylation mediated by FUCA1 is involved in tumor suppression. Abstract : We show that a p53 target gene, FUCA1, encodes a fucosidase and has a tumor suppressive function. Expression of FUCA1 suppressed the growth of cancer cells and induced cell death in a manner dependent on its enzymatic activity. Furthermore, we showed that expression of FUCA1 reduced the fucosylation and activation of EGFR, and concomitantly suppressed downstream EGF signaling pathways. In addition, we found that loss‐of‐function mutations in FUCA1 occur in some cancers, as well as reduced expression. Low FUCA1 expression is also associated with poorer prognosis in cancer patients. These results collectively suggest that defucosylation by FUCA1 contributes to tumor suppression, and thus identifies a novel mechanism of tumor suppression that involves FUCA1‐mediated protein defucosylation.